The legal methodology of the Salafi movement in Egypt - Wright, Brian (AUC Knowledge Fountain, 2012)
This study derives the legal methodology of the modern Salafi movement in Egypt. The first two sections develop context, pondering global Salafism as well as the effects of the Egyptian political, economic, and cultural spheres on the movement's development, while the third section discusses the legal opinions of Salafi preachers in the fields of democracy, law, economics, women's rights, non-Muslims, Al Azhar, the Shi'a, as well as the arts and leisure. Section four synthesizes these opinions to create the general approach of the movement to Islamic Law. This study suggests that each manifestation of Salafism is the result of local circumstances, and not part of a global movement. In Egypt, the failures of Nasserism and capitalism in the 20th Century resulted in calls for a return to Islam, particularly following the 1967 war. Influenced by political Islam as well as Saudi Wahhabism, this group of young preachers would grow over the next thirty years to re-define the country's religious landscape. The legal methodology of the Salafi movement is one of selective literalism of the Qur'Ä n and Sunna, without a defined framework such as that of UsÅ«l al Fiqh. There is an emphasis on issues of theology and a lack of understanding of modern politics and economics. This creates a disconnection with issues on the ground and causes instability in the movement as they increase their political participation. However, a sense of malleability in legal rulings allows the movement to adapt to changing political conditions and provides a method to remain relevant.